Financing Educational Institutions from the Perspective of Edupreneurship in the Digital Era - Holilur Rahman; Fina Alaillah; Ansisca Ansisca; Aishmah Naily Fauziyah; Annatul Aini (Penerbit Hellow Pustaka, 2026)
Digital transformation has brought significant changes in education governance, including accountability, transparency, and the effectiveness of financial management. However, many educational institutions still face obstacles such as reliance on manual systems, low digital literacy, and lack of use of financial technology. The edupreneurship approach offers solutions through funding innovation, diversification of funding sources, business unit development, and digital fundraising that can strengthen the sustainability of the institution. In this study, a descriptive qualitative method with a literature study was used to identify key concepts, research findings, and relevant financing models. The results of the study show that education financing has a strategic role in ensuring the smooth operation of institutions, improving the quality of education services, strengthening planning and accountability, ensuring equitable access to education, optimizing philanthropy, and providing economic and social benefits for the community. In addition, the integration of digitalization and edupreneurship has proven to be able to encourage transparency while opening up innovative funding opportunities, although there are still challenges in the form of infrastructure gaps and limited human resources. This study confirms that there is a research gap in the integration of the two approaches, so a financing management model that combines the power of technology and entrepreneurial innovation is needed to support the sustainability of educational institutions in the digital era.